Polychlorinated biphenyls (PCBs) in sediments from the western Adriatic Sea: Sources, historical trends and inventories - Combi, Tatiane; Miserocchi, Stefano; Langone, Leonardo; Guerra, Roberta (The Science of the total environment, 2016)
Sources, historical trends and inventories of polychlorinated biphenyls (PCBs) were investigated in sediments collected in five transects along the north-south axis of the western Adriatic Sea. The concentration of total PCBs (∑28 PCBs) ranged from <LOD (limit of detection) to 9.0ngg−1 in the sediment cores and between 0.1 and 2.2ngg−1 in recent sediments. Chronological records of PCB concentrations displayed a common pattern with historical PCB production and use, with the maximum peak values detected between the 1960s and the 1980s. Sediments deposited within the last two decades presented a ~40% to ~80% PCB reduction in comparison to the peak levels, reflecting the ban on PCB production and use since the late 1970s. PCB levels along with the presence of high-chlorinated congeners decreased southwards, indicating the Po River as the major source of PCBs in the western Adriatic Sea. This is further corroborated by the estimated inventories of PCBs, which were ~4–7 times higher in the Po River prodelta (256ngcm−2) in comparison to the middle and southern Adriatic, respectively, and about 100 times higher than the in the deep Adriatic Sea. [Display omitted] •PCBs were determined in recent and dated sediments from the western Adriatic Sea.•Unprecedented data of PCB levels, historical trends and inventories were assessed.•PCB historical trends corresponded to their production and use over time.•Congener composition indicates the Po River as the major contributor of PCBs.•High-chlorinated PCBs in the deeper Adriatic suggest influence of cascading process.